Meta Analysis: Factors Affecting Implementation of Self-Care Practice in Diabetes Mellitus Patients - Khairiyyah, Alimah Ulfah; Nazalah, Rajba; Aditya, Stefanus; Murti, Bhisma; Marsim, Etanaulia (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by high blood sugar levels. If not controlled properly, diabetes mellitus can cause serious complications. Self-care practices are a very important factor in controlling the disease. This study aims to estimate the factors that influence self-care practices in diabetes sufferers.Subjects and Method: This was a systematic review and meta-analysis using PICO format. Population: diabetes patients. Intervention: having diabetes knowledge, high social support, female gender and presence of comorbidities. Comparison: no diabetes knowledge, low social support, male gender and no comorbidities. Outcome: self-care practices. The articles used in this research came from 5 databases, namely Google Scholar and Science Direct. The keywords of the article are